Different Positive Electrodes for Anode-Free Lithium Metal Cells. Issue 4 (1st April 2022) - Louli, A. J.; Eldesoky, A.; deGooyer, Jack; Coon, Matt; Aiken, C. P.; Simunovic, Z.; Metzger, M.; Dahn, J. R.
Abstract : With a potential to deliver 60% greater energy density than conventional lithium-ion batteries, the simple design of anode-free lithium metal cells with liquid electrolytes has generated significant research interest. However, without excess lithium, the short lifetime and safety concerns for cells cycling lithium metal with liquid electrolytes make the development of anode-free cells particularly challenging. Herein, we investigate the effect of four different positive electrode materials on the performance of anode-free cells—LiNi0.5 Mn0.3 Co0.2 O2 (NMC532), LiNi0.8 Mn0.1 Co0.1 O2 (NMC811), LiCoO2 (LCO), and LiFePO4 (LFP). In-situ electrochemical impedance spectroscopy and electrolyte degradation measurements were performed on cells with dual-salt LiDFOB/LiBF4 electrolyte to elucidate cell failure. Additional state-of-the-art electrolyte systems as well as other testing conditions (temperature, pressure, depth of discharge) were also explored, along with nail safety tests and calendar aging cycle-hold experiments. We show that the rate of lithium inventory loss and impedance growth differs amongst these cell chemistries, ultimately resulting in the shortest lifetime for NMC811 and the longest lifetime for LCO anode-free cells of 200 cycles.